Evaluasi Program Sertifikasi CHSE Desa Wisata Dalam Pembangunan Pariwisata Berkelanjutan - Wulandari, Septi; Septian, Esa (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
This study aims to evaluate the effectiveness of the CHSE (Cleanliness, Health, Safety, Environment) Certification Program implemented in tourist destinations in Sleman Regency for the recovery of the tourism sector post-COVID-19 pandemic. Using a qualitative approach with a case study method, this research collects data through literature review and policy analysis, focusing on the input, output, and outcome indicators of the program. The findings show that the CHSE program can enhance tourists' trust in the cleanliness and safety of tourist destinations. However, significant challenges were found in its implementation, particularly in tourist destinations and village tourism, which have not fully understood the certification procedures and face financial constraints. The implications of this study highlight the importance of improving training, socialization, and technical support for destination managers to expand the application of CHSE, especially in village tourism. This research contributes to the literature on the recovery of the tourism sector in Indonesia by emphasizing the challenges of implementing CHSE certification at the destination level, which is crucial for sustainable tourism policies.